Tinjauan Yuridis Terhadap Perlindungan Konsumen Atas Beredarnya Makanan Kadaluarsa - Rahmatullah, Adin; Muh. Iman, Muh. Iman (Indonesian Journal of Law and Justice, 2023)
Regulations governing consumer rights should be able to protect consumers from abuse by business actors. Information for consumers is very important, because if inadequate information is conveyed to consumers, it is also a product defect known as defective instructions or inadequate information in order to avoid losses due to errors in consuming existing products. This right can also be linked to the right to comfort, security and safety for consumers of goods or services, especially regarding expired packaged food products. Information which is one of the consumer's rights is related to several things, including the benefits of using the product, side effects of using the product, expiry date, the contents of the product, and the identity of the manufacturer of the product. This information can be conveyed verbally or in writing, either by including it on the label attached to the product packaging, or through advertisements delivered by the manufacturer, both through print and electronic media.